Tracing the sources of floating plastic in Romanian waters under changing regional pressures through backtracking modeling - Leidy M. Castro-Rosero; Ivan Hernandez; Maria Liste; Jose M. Alsina; Manuel Espino; Iulian Pojar; Dan Vasiliu (Science of The Total Environment, 2025)

Numerical modeling of the dispersion and accumulation of marine litter from the Dniester River in coastal areas of the northwestern Black Sea - Leidy M. Castro-Rosero; Ivan Hernandez; Marc Mestres; Maria Liste; Jose M. Alsina; Manuel Espino (Marine Pollution Bulletin, 2025)

Spatial Variability Analysis of Renewal Time in Harbour Environments Using a Lagrangian Model - Yaiza Samper; Ivan Hernández; Leidy M. Castro-Rosero; Maria Liste; Manuel Espino; José M. Alsina (Journal of Marine Science and Engineering, 2025)
The water quality in port domains is highly dependent on the capacity for renewal and mixing with external water. This study uses Lagrangian modelling to investigate renewal time in Barcelona, Tarragona, and Gijón harbours (Spain), which represent semi-enclosed micro-tidal and meso-tidal environments. For this purpose, different particle-tracking simulations have been carried out in each of the ports to study the trends of circulation and water renewal trends both on the surface layer and at the bottom. The results indicate that in microtidal Mediterranean ports, the renewal time is longer at the bottom (32 days in Barcelona and 61 days in Tarragona). Conversely, in the mesotidal port of Gijón, located on the Cantabrian coast, the opposite pattern is observed, with higher renewal times at the surface (14 days). While the results from Lagrangian modelling exhibit magnitudes comparable to in situ measurements from previous studies, it remains essential to evaluate the specific characteristics of each method and compare these findings with other similar works.

Surveillance Plan of Lipophilic Marine Biotoxins in Molluscs from the Croatian Coast - Tanja Bogdanovic; Federica Di Giacinto; Miriam Berti; Pierina Visciano; Sandra Petričević; Mario Rogošić; Zoran Rogić; Giuseppina Mascilongo; Ludovica Di Renzo; Nicola Ferri; Maria Schirone; Eddy Listes (Exposure and Health, 2022)

Evaluation of the Operational CMEMS and Coastal Downstream Ocean Forecasting Services During the Storm Gloria (January 2020) - Marcos G. Sotillo; Baptiste Mourre; Marc Mestres; Pablo Lorente; Roland Aznar; Manuel García-León; Maria Liste; Alex Santana; Manuel Espino; Enrique Álvarez (Frontiers in Marine Science, 2021)
Storm Gloria was the 10th named storm in Europe for the 2019–2020 winter season, and it severely affected Spain and France. This powerful storm represents an excellent study case to analyze the capabilities of the different ocean model systems available in the Spanish Mediterranean coasts to simulate extreme events, as well as to assess their suitability to enhance preparedness in maritime disasters with high impacts on coastal areas. Five different operational ocean forecasting services able to predict the storm-induced ocean circulation are evaluated. Three of the systems are delivered by the Copernicus Marine Service (hereafter CMEMS): the CMEMS global scale solution (GLO-1/12°), the specific Mediterranean basin scale one (MED-1/24°), and the regional solution for the Atlantic façade (IBI-1/36°), which includes also part of the western Mediterranean. These CMEMS core products are complemented with two higher resolution models focused on more limited areas, which provide operational forecasts for coastal applications: the WMOP system developed at the Balearic Islands Coastal Observing and Forecasting System (SOCIB) with a horizontal resolution of roughly 2 km and the Puertos del Estado (PdE) SAMOA systems with a 350-m resolution that cover the coastal domains of the Spanish Port Authorities of Barcelona, Tarragona, Castellón and Almeria. Both the WMOP and SAMOA models are nested in CMEMS regional systems (MED and IBI, respectively) and constitute good examples of coastal-scale-oriented CMEMS downstream services. The skill of these five ocean models in reproducing the surface dynamics in the area during Gloria is evaluated using met-ocean in situ measurements from numerous buoys (moored in coastal and open waters) and coastal meteorological stations as a reference to track the effects of the storm in essential ocean variables such as surface current, water temperature, and salinity throughout January 2020. Furthermore, modeled surface dynamics are validated against hourly surface current fields from the two high-frequency radar systems available in the zone (the SOCIB HF-Radar system covering the eastern part of the Ibiza Channel and the PdE one at Tarragona, which covers the Ebro Delta, one of the coastal areas most impacted by Gloria). The results assess the performance of the dynamical downscaling at two different levels: first, within the own CMEMS service (with their regional products, as enhanced solutions with respect to the global one) and second in the coastal down-streaming service side (with very high-resolution models reaching coastal scales). This multi-model study case focused on Storm Gloria has allowed to identify some strengths and limitations of the systems currently in operations, and it can help outlining future model service upgrades aimed at better forecasting extreme coastal events.